Purification and properties of buffalo (Bubalus bubalis) erythrocyte hexokinase - Cesar, M. D.; Colepicolo, P.; Rosa, C. D.; Rosa, R. (Elsevier B.V., 1997)
Buffalo erythrocytes contain one isozyme of hexokinase that apparently lacks microheterogeneity as shown by chromatographic properties. A single protein band was detected by means of Western blotting using an antibody raised in rabbits against homogeneous rat brain hexokinase I. The native protein has a molecular weight of 200,000 +/- 2880 by gel filtration. Partial purification of erythrocyte hexokinase by a combination of several procedures, including affinity chromatography, which was previously applied successfully to the purifica tion of other mammalian type I hexokinases, produced a partially purified enzyme that showed several contami nants after SDS-polyacrylamide gel electrophoresis. The affinity of buffalo erythrocyte hexokinase for glucose (K-m = 0.012 +/- 0.001 mM) is lower than most other mammal hexokinases type I. It phosphorylates other sugars, with considerably higher K-m values. This isozyme is able to use MgATP but does not use MgGTP, MgCTP or MgUTP. We used inhibition patterns, obtained with products to elucidate enzyme sequential mechanisms. Our results are clearly in agreement with a random sequential mechanism and in disagreement with an ordered sequential mechanism with either glucose or ATP as the obligatory first substrates. The ADP inhibition was of mixed type with both ATP and glucose as substrates. (C) 1997 Elsevier B.V.
Keywords: buffalo; erythrocyte; hexokinase; kinetics; inhibition; mechanism; phosphorylation; glucose-6-P